Capital Punishment in the United States, 1973-1991 ([Verlag nicht ermittelbar], 1995)
This data collection provides annual data on prisoners under a sentence of death and on those whose offense sentences were commuted or vacated during the period 1973-1991. Information is supplied for basic sociodemographic characteristics such as age, sex, race, ethnicity, marital status at time of imprisonment, level of education, and state of incarceration. Criminal history data include prior felony convictions for criminal homicide and legal status at the time of the capital offense. Additional information is available for inmates removed from death row by yearend 1991 and for inmates who were executed.